The UN and the Smile of an Actress - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Népszabadság article on the US getting film star Myrna Loy to hand over a petition to the Thai Prince, 14 September 1957.